SEROLOGICAL MARKERS OF CELIAC DISEASE AND HLA II ANTIGENS IN CHILDREN AND ADOLESCENTS WITH DIABETES MELLITUS TYPE 1 - E. O. Hennesy; T. L. Kuraeva; S. A. Prokofyev; N. B. Smirnova; Y. V. Tishina; E. V. Тitovic; V. A. Peterkova (Вопросы современной педиатрии)
We have studied incidenceof immunological markers of celiac disease in children with diabetes mellitus type 1 (DM1) and their correlation with clinical peculiarities and polymorphous alleles of HLA. It was shown that incidence of celiac markers is higher in DM1 children than in general population and makes up 7.4%. Patients who were seropositive with celiac antigens had gastrointestinal symptoms and iron deficiency more often. The occurrence rate of other autoimmune disorders in seropositive patients was 24%, with high count of autoantibodies towards transglutaminase (AbTT) — 50%. More than 78% of seroposetive patients possessed haplotypes DQ2 and|or DQ8 HLA. The occurrence rate was identical. In patients with high AbTT occurrence of HLA genotypes with DQ2 and/or DQ8 rose up to 100%.